Predictors of posttraumatic growth among conflict-related sexual violence survivors from Bosnia and Herzegovina - Kimberley Anderson; Amra Delić; Ivan Komproe; Esmina Avdibegović; Elisa van Ee; Heide Glaesmer (Conflict and Health, 2019)
Abstract Background Conflict-related sexual violence (CRSV) was committed on a large scale against women across Bosnia and Herzegovina (BiH) during the 1990’s war, and research has shown both negative and positive psychosocial outcomes following such acts of interpersonal violence. We aim to determine the capacity for posttraumatic growth (PTG) among a population of women who experienced CRSV, and to what extent it is impacted by factors such as coping and optimism. Methods This study sought to examine the relationship between PTG (posttraumatic growth inventory), symptoms of posttraumatic stress disorder (PTSD; Harvard Trauma Questionnaire) and dispositional factors such as coping (COPE) and optimism (Life-Orientation Test-Revised) in a sample of n = 104 women. We first conducted bivariate correlations and then hierarchical linear regression analyses, and hypothesized that approach coping strategies and optimism will act to enhance PTG. Results Findings showed that the average total score for PTG in this study was 58.94 (SD = 23.01), and current PTSD symptomatology above a threshold of > 2.5 was detected in 92.3% (n = 96) participants (mean score 3.18, SD = .45). Bivariate correlations showed that higher levels of PTG were associated with greater optimism, greater approach coping strategies positive reinterpretation and planning, and lower avoidance strategies behavioural disengagement and substance use. When entered into a regression model, only positive reinterpretation and behavioural disengagement remained, the R-square of the total set of predictors was 0.16, thus explaining 16% of PTG total score. Conclusion Two types of coping (namely capacity of both greater positive reinterpretation and lower behavioural disengagement) most strongly predicted growth after trauma in this sample of CRSV survivors from BiH. These dimensions of coping confirm the role of coping strategies in the development of PTG. Further research would be useful in corroborating these findings in other post-conflict settings, and delving further into the possibility of a dual mechanism of growth and distress after CRSV.